Mrs. Creamer and family tending a garden, Dawson, Yukon Territory, spring 1905. - University of Washington Libraries. Special Collections Division
PH Coll 246.300 [Meed journal: "Mrs. Creamer & family. Spring Gardening. Dawson, Y.T. 1905"] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number